2019
DOI: 10.4274/tjps.57805
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rusa unicolor Antler Extracts from East Kalimantan in Bone Turnover Cell Models

Abstract: Objectives: Osteoporosis is a disease described by a skeletal degradation of bone tissue domination to increase risk of fracture. Traditionally, Rusa unicolor antler from East Kalimantan is used to treat many kinds of diseases, and one of them is disease related to bone turnover. The present research aims to analyze the effects of 70% ethanol and aqueous extracts of Rusa unicolor antler from East Kalimantan on nitric oxide inhibition, osteoblast differentiation, and mineralization related to bone turnover. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The absorbance was ruminated at 570 nm by an enzyme-linked immunosorbent assay (ELISA) reader. All experiments were performed in triplicate, with the relative cell viability (%) declared as a portion relative to the unprocessed control cells [15,16].…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance was ruminated at 570 nm by an enzyme-linked immunosorbent assay (ELISA) reader. All experiments were performed in triplicate, with the relative cell viability (%) declared as a portion relative to the unprocessed control cells [15,16].…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…After incubation, the cell lysates were examined for ALP by adding 200 µL of p-nitrophenyl phosphate (PNPP) and diethanolamine buffer into each well for a period of 30 min and at room temperature. The 50 µL/well stop solution was inserted to stop the reaction while ELISA reader at 405 nm was applied to measure the absorbance [15,16].…”
Section: Differentiation Of Cellular Alkaline Phosphatase Activity (Alp)mentioning
confidence: 99%
“…Some clinical evidences recommend a role for phytoestrogen in the therapy of osteoporosis [12][13][14][15]. Previous studies showed that 70% ethanol and aqueous extracts of deer antler from East Kalimantan increased the alkaline phosphatase (ALP) and mineralization activities of 7F2 cell that is an osteoblast cell lines [16,17]. These extracts contain several major constituents such as protein, lipids, ash, calcium, collagen, chondroitin sulfate and glucosamine [18,19].…”
Section: Introductionmentioning
confidence: 99%